2022
DOI: 10.1038/s41467-022-28490-7
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragmentation impacts the seasonality of Amazonian evergreen canopies

Abstract: Predictions of the magnitude and timing of leaf phenology in Amazonian forests remain highly controversial. Here, we use terrestrial LiDAR surveys every two weeks spanning wet and dry seasons in Central Amazonia to show that plant phenology varies strongly across vertical strata in old-growth forests, but is sensitive to disturbances arising from forest fragmentation. In combination with continuous microclimate measurements, we find that when maximum daily temperatures reached 35 °C in the latter part of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 88 publications
0
48
0
Order By: Relevance
“…Similarly, fractions of deciduous species increase with tree size class (Condit et al, 2000;Meakem et al, 2018). Even in evergreen tropical forests, seasonal variation in leaf quantities follows distinct vertical patterns throughout the vertical profile depending on height and light environments (Tang & Dubayah, 2017;Smith et al, 2019;Nunes et al, 2022). For instance, in a central Amazonian forest, the upper canopies of both interior and edge forests shed leaves when maximum daily T air exceeded c. 35°C (Nunes et al, 2022).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, fractions of deciduous species increase with tree size class (Condit et al, 2000;Meakem et al, 2018). Even in evergreen tropical forests, seasonal variation in leaf quantities follows distinct vertical patterns throughout the vertical profile depending on height and light environments (Tang & Dubayah, 2017;Smith et al, 2019;Nunes et al, 2022). For instance, in a central Amazonian forest, the upper canopies of both interior and edge forests shed leaves when maximum daily T air exceeded c. 35°C (Nunes et al, 2022).…”
Section: Reviewmentioning
confidence: 99%
“…Thus, for example, increases in canopy temperature reduce forest GPP in the tropics (Pau et al ., 2018). Yet, evidence also suggests GPP and ecosystem respiration are less sensitive to heat and drought stress in older forests than in young forests (Xu et al ., 2020), perhaps in part because of more complex vertical structuring (Jones et al ., 2019; Nunes et al ., 2022). A rare example of a study comparing climate sensitivity of C fluxes across size classes (Meakem et al ., 2018) showed that M woody was more strongly elevated among large than small trees during an El Niño drought in Panama, while the smallest trees had higher productivity during the drought, likely because of increased light in the understory.…”
Section: Review Of Vertical Gradientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, several studies have demonstrated that it was possible to characterize circadian branch movement of boreal trees from overnight TLS measurements (Campos et al, 2021;Junttila et al, 2022;Puttonen et al, 2016Puttonen et al, , 2019. High temporal resolution TLS data have also been used for studying leaf phenology in a temperate deciduous forest with one to three weekly TLS measurements (Calders et al 2015) and in the tropics with TLS point clouds acquired every-two weeks spanning (Nunes et al 2022). However, it is still unknown whether TLS, or terrestrial point clouds in general, can be used to capture the seasonal growtha fundamental time span in the forest growth processof boreal trees.…”
Section: Introductionmentioning
confidence: 99%